Performance Optimization and Synergistic Mechanism of Ternary Blended Cementitious System Composed of Fly Ash, Slag, and Recycled Micro-Powder - Rongfang Song; Qingnian Yang; Hang Song (Buildings)
The blended system of solid waste micro-powders is of great significance for the efficient utilization of recycled micro-powder. In this study, a ternary blended cementitious system composed of fly ash, slag, and recycled micro-powder was constructed, and its effects on the workability, mechanical properties, shrinkage performance, and microstructure of recycled mortar were systematically investigated. The experimental results show that with the increasing dosage of slag and recycled micro-powder (partially replacing cement and fly ash), the standard consistency water demand of the cementitious system decreases and the setting time is prolonged. When the replacement levels of recycled micro-powder and slag are both 10%, the 3-day, 7-day, and 28-day mechanical strengths of the mortar specimens are comparable to those of the reference group, with an increased flexural-to-compressive strength ratio and improved brittleness. SEM and mercury intrusion porosimetry (MIP) analyses revealed that systems incorporating low addition levels of recycled micro powder and slag powder exhibit calcium silicate hydrate (C-S-H) gel, acicular ettringite crystals, and a denser pore structure. However, at higher dosages (>10%), the porosity increases significantly and the pore structure deteriorates, resulting in reduced shrinkage performance. Overall, when the replacement rate of cement–fly ash by recycled micro-powder and slag is 10%, the ternary blended system exhibits optimal macroscopic performance and microstructure, providing a scientific basis for the resource utilization of solid waste.